A Philosophical Dictionary, Volume 02 - Voltaire, 1694-1778; Leigh, Oliver Herbrand Gordon; Morley, John, 1838-1923; Smollett, T. (Tobias), 1721-1771; Fleming, William F. (Salt Lake City, UT : Project Gutenberg, 2011)
"A Philosophical Dictionary, Volume 02" by Voltaire is an encyclopedic dictionary published in 1764. This alphabetically arranged work challenges religious and social institutions through sharp, often provocative articles. Born from a dinner party game at Frederick II's court, Voltaire crafted a deliberately pocket-sized, affordable text to spread revolutionary ideas. The dictionary reflects his advocacy for tolerance, freedom of press, and deism while criticizing religious fanaticism. Though beloved by Enlightenment rulers and the public, religious authorities condemned it, burning copies across Europe while Voltaire remained calmly anonymous. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Dictionnaire_philosophique
Release date is 2011-03-28
Produced by Andrea Ball, Christine Bell & Marc D'Hooghe (From images generously made available by the Internet Archive.)
Keywords: Philosophy -- Dictionaries; Criticism (Philosophy)